Estrategia Y Compromiso Directivo: Condiciones Para Reestructurar Una Organización - Kertész, Víctor (European Scientific Journal, ESJ, 2016)
The purpose of this study is the successful achievement of an organizational restructuring, specifying the key factors of success, identifying the necessary conditions and exposing the implementation tools. When organizations decide their restructuration in the event of a crisis, they frequently fail, usually because the commitment of top management is not present regarding the application of leadership, decision-making and communication. The concept of corporate restructuring (Biasca, 1991) refers mainly to financial processes and reducing personnel, and others, like Kotter (2002), point to the strategic and cultural change. According to the proposed approach, top management defines the strategy, and the middle management applies it. The appropriate tools are: the SWOT analysis, the products and markets development matrix, the Porter matrix, etc.